2016
DOI: 10.1097/lgt.0000000000000174
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study of Human Papillomavirus Vaccine Utilization Among University Women

Abstract: Human papillomavirus vaccine is highly acceptable among college women, particularly among Hispanic women. Efforts to vaccinate should include time of college enrollment. Such efforts are critical for the large scale prevention of cervical cancer and its precursor lesions and ultimately for preventable cervical cancer mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…This is important because previous research in female college students found that greater knowledge about HPV was associated with willingness to receive the vaccine [ 22 ]. Other studies have found a similar relationship between knowledge and HPV vaccination intention and uptake [ 23 24 ]. While 63.2% of the students indicated that they were in a relationship and 63.4% indicated that they have had sexual intercourse, students reported relatively low levels of perceived risk related to HPV.…”
Section: Discussionsupporting
confidence: 62%
“…This is important because previous research in female college students found that greater knowledge about HPV was associated with willingness to receive the vaccine [ 22 ]. Other studies have found a similar relationship between knowledge and HPV vaccination intention and uptake [ 23 24 ]. While 63.2% of the students indicated that they were in a relationship and 63.4% indicated that they have had sexual intercourse, students reported relatively low levels of perceived risk related to HPV.…”
Section: Discussionsupporting
confidence: 62%
“…Our results mostly aligned with the results of previous surveys, 34,37 -40,42 although not completely, particularly among Hispanic women, whom we found to be more reticent than White women about vaccination. Compared with White women, Black women in our sample were less likely to intend to receive maternal and infant vaccines.…”
Section: Discussionsupporting
confidence: 90%
“…38,39 In addition, although Hispanic people are more likely than non-Hispanic White people to be concerned about serious adverse effects of human papillomavirus vaccines, they are also more likely to follow their physician's recommendation to vaccinate. 40,42 However, these surveys were given to parents and focused on infant and adolescent vaccines, as opposed to pregnant women with a focus on maternal vaccines.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, however, we identified a subgroup of women, albeit small, who were generally highly educated, considered their HPV-knowledge to be good, but did not realistically identify their own elevated risk of developing cervical cancer without regular gynecologic follow-up. Underestimation of one’s own cervical risk has been described among some university educated women in the U.S. [ 30 , 31 ]. On the other hand, there is also a report that university educated women diagnosed with HPV were likely to consider themselves at risk for developing cervical cancer [ 32 ].…”
Section: Discussionmentioning
confidence: 99%